MOLECULAR CHARACTERIZATIONS OF POTATO SOMATIC HYBRIDS BY INTER SIMPLE SEQUENCE REPEAT (ISSR) MARKERS - tiwari, jagesh kumar (Potato Journal, 2016)
Diverse gene pool is of one of the breeding objectives of potato breeding programme. Although, Solanum species offers wide diversity, breeders exploited only a limited scale in breeding. In the present study, interspecific potato somatic hybrids, developed via somatic hybridization using wild Solanum species, were employed for molecular characterization. Interspecific potato somatic hybrids of the Solanum tuberosum ‘C-13’ (+) S. pinnatisectum; and C-13 (+) S. etuberosum were characterised using inter simple sequence repeats (ISSR) markers for their nuclear constitutions. A total of 16 ISSR primers were used to characterize the somatic hybrids. In the somatic hybrids S. tuberosum (+) S. pinnatisectum, out of total 149 bands, 100 polymorphic and 49 monomorphic bands were amplified, whereas in the somatic hybrids S. tuberosum (+) S. etuberosum, out of total 168 bands, 130 polymorphic and 38 monomorphic bands were amplified. As a result, ISSR markers confirmed hybridity of the somatic hybrids by possessing parent-specific bands.